A review on the fatigue behavior of Ti-6Al-4V fabricated by electron beam melting additive manufacturing. (February 2019) - Chern, Andrew H.; Nandwana, Peeyush; Yuan, Tao; Kirka, Michael M.; Dehoff, Ryan R.; Liaw, Peter K.; Duty, Chad E.
Highlights: As-fabricated horizontally orientated parts show greater fatigue life than vertical. Machining improves overall fatigue life and reduces anisotropic fatigue behavior. Post EBM-fabrication HIP alone does not universally improve fatigue life. Machined and HIPed EBM parts show comparable fatigue life to conventional Ti-6Al-4V. Abstract: Electron beam melting (EBM) is a rapidly-developing metal additive manufacturing process that holds significant interest in the aerospace and biomedical industries for the high-strength titanium alloy, Ti-6Al-4V. These industries have fatigue-limited applications, but a lack of understanding of the EBM process-microstructure-fatigue relationships limit widespread use and presents challenges for certification. In this review, uniaxial fatigue data was collected and the effects of build orientation, surface roughness, and hot-isostatic pressing are linked to the fatigue properties highlighting microstructure, defects, and failure mechanisms. The observations and conclusions are supported by statistical analysis using the mean fatigue life obtained by the Statistical Fatigue-Limit Model. Both EBM-process and post-process structure relationships are discussed in order to identify the best-practice for fatigue-resistant design. The performance of the EBM material is compared to conventionally manufactured Ti-6Al-4V and possible methods to increase the fatigue resistance are discussed. Anisotropic fatigue behavior was observed in as-fabricated parts and no statistical distinction was found in the fatigue performance of HIPed and as-fabricated material provided the same as-fabricated rough surface condition. However, comparable fatigue life to traditionally manufactured lamellar Ti-6Al-4V is achieved when both post-process HIP and machining are applied to EBM-fabricated parts.